Performance evaluation of maize starch as a multifunctional excipient in metronidazole tablet formulation - Yonni Eshovo Apeji; Ali Abdulhakim; Sophie Nock Anyebe; Oluwaseun Adenike Orugun; Adeniji Kehinde Olowosulu; Avosuahi Rukayat Oyi (Facultad de Farmacia, Universidad de Granada, 2020)
ABSTRACT Objective: The aim of this study was to evaluate the performance of maize starch as a multifunctional excipient in metronidazole tablet formulation. Methods: Metronidazole tablets were prepared by wet granulation containing maize starch as diluent (40 %), disintegrant (10 %), and binder (5 %) and compared with a reference formulation containing lactose as diluent (40 %), maize starch as disintegrant (10 %) and acacia as binder (5 %). The granules were analysed for particle size, flow properties, compressibility and moisture content. Tablets weighing 500 mg were compressed for both formulations on a Single Punch Tablet Press using a 12 mm flat-faced punches at 57.5 MPa. The tablets were kept for 24 h to allow for elastic recovery and evaluated for weight and content uniformity, thickness, crushing strength, friability, disintegration time and in vitro drug release. Results: The granule properties revealed differences in mean granule size, angle of repose, bulk and tapped densities for both formulations. Batch I tablets gave rise to better tableting properties compared to batch II tablets. Conclusion: This study confirms the suitability of maize starch as a multifunctional excipient in tablet formulation.